Location of Sternal Fractures as a Possible Marker for Associated Injuries. (13th November 2013) - Scheyerer, Max J.; Zimmermann, Stefan M.; Bouaicha, Samy; Simmen, Hans-Peter; Wanner, Guido A.; Werner, Clément M. L.
Abstract : Introduction . Sternal fractures often occur together with serious and life-threatening additional injuries. This retrospective study was designed to assess concomitant injuries and develop a correlation between fracture location and the severity of injury. Methods. All patients (n = 58 ) diagnosed with a fracture of the sternum by means of a CT scan were analysed with respect to accident circumstances, fracture morphology and topography, associated injuries, and outcome. Results . Isolated sternal fractures occurred in 9%. In all other admissions, concomitant injuries were diagnosed: mainly rip fractures (64%), injury to the head (48%), the thoracic spine (38%), lumbar spine (27%), and cervical spine (22%). Predominant fracture location was the manubrium sterni. In these locations, the observed mean ISS was the highest. They were strongly associated with thoracic spine and other chest injuries. Furthermore, the incidence of head injuries was significantly higher. ICU admission was significantly higher in patients with manubrium sterni fractures. Conclusion . Sternal fractures are frequently associated with other injuries. It appears that the fracture location can provide important information regarding concomitant injuries. In particular, in fractures of manubrium sterni, the need for further detailed clinical and radiologic workup is necessary to detect the frequently associated injuries and reduce the increased mortality.